STUDENT ATTITUDE TOWARD ACTIVATING BACKGROUND KNOWLEDGE IN READING - Fadilla Stephanie Dwi; Hawalaina Rahman Hasan Siregar; Emeliya Sukma Dara Damanik (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Reading is one of the skills that every student must have in order to comprehend what they are reading. Background knowledge is required for students to use in their reading strategy. Background knowledge is information that a person has about a topic that is based on his experience, for example. The purpose of this study is to investigate the impact of reading strategies on background knowledge among English Education Departments at State Islamic University of North Sumatera. The researcher's sample consists of several in third semester students of English Education Departments at State Islamic University of North Sumatera. In this study, researchers used quantitative methods such as questionnaires and tests to conduct surveys. The questionnaire was an open questionnaire with two sessions. And the data found in this study revealed that the students attitude toward using the Activating background knowledge strategy in third semester students of English Education at State Islamic University of North Sumatera is still immature. They have not been able to successfully apply this strategy when reading a text. Students' attitudes toward using this strategy remain weak and negative. Students are still having difficulty activating their background knowledge.